INDIA AND THAILAND RELATIONS IN THE 21ST CENTURY - N. Surjitkumar; Anal, Koning Hrangbung (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the dynamic and multifaceted relationship between India and Thailand, emphasizing their strategic, historical, cultural, and economic ties from 2000 to 2022. It explores key areas such as historical interactions, people-to-people contact, and the pivotal role of the Indian Diaspora in Thailand. The study highlights shared cultural heritage, collaborative regional frameworks like ASEAN and BIMSTEC, and connectivity initiatives including the India-Myanmar-Thailand Trilateral Highway. Analyzing the influence of soft power and cultural diplomacy, the research underscores how both nations serve as crucial partners in linking South and Southeast Asia, fostering regional stability, development, and mutual understanding.